Meibomian gland dropout and ocular surface appearances of young adults in Kuala Lumpur - Mohamad Hanif Hajar Maidin,; Bariah Mohd-Ali,; Zainora Mohammed,; Jamaludin Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Meibomian gland dropout (MGDo) refers to partial or total loss of the acinar tissues which can be detected by meibography. It is possible that MGDo can be associated with lid margin inflammation commonly seen in dry eye (DE) patients. This study evaluated the MGDo and its association with lid margin inflammation in young adults using meibography and lid wiper epitheliopathy (LWE) techniques. Other ocular surface appearance (cornea, conjunctiva and limbus) were also examined. A total of 107 healthy noncontact lens wearers were evaluated (mean age: 23.06 ± 2.63 years old). All subjects were screened with McMonnies Dry Eye Questionnaire (MDEQ) before undergoing clinical investigations using slit-lamp biomicroscope, LWE and meibography. Cornea, conjunctiva and limbus appearances were graded using the Efron grading scale. Following the MDEQ score, 36 subjects were classified as DE (mean 16.49 ± 1.74), and 71 subjects were classified as non-DE (NDE, mean score: 7.23 ± 3.09). The difference in corneal staining between both groups was significant (χ2 [1, N = 107] = 18.01, p < 0.05). A total of 70% of subjects had LWE staining which was more apparent in subjects with DE (χ2 [1, N = 107] = 13.17, p < 0.01). The meiboscore indicated that 44.85% of subjects had MGDo, with a higher percentage (72.22%) in DE. There were significant differences between meiboscore in both groups (χ2 [1, N = 107] = 16.42, p < 0.05). However, there was weak and insignificant correlation between LWE and meiboscore (rs = 0.14, p = 0.16). Positive correlations were noted between MDEQ and LWE (rs = 0.49, p < 0.01), MDEQ and corneal staining (rs = 0.36, p < 0.01) and MDEQ and meiboscore (rs = 0.24, p < 0.05). The results of this study demonstrated the differences in MGDo, LWE and ocular surface appearances between DE and NDE of the young adults but MGDo was not associated with LWE. Larger number of subjects is needed to confirm these findings.